Waggle needling wields preferable neuroprotective and anti-spastic effects on post-stroke spasticity rats by attenuating γ-aminobutyric acid transaminase and enhancing γ-aminobutyric acid. Issue 10 (10th July 2020) - Wang, Jun-Xiang; Mu, Jie-Dan; Ma, Liang-Xiao; Sun, Tian-Yi; Qian, Xu; Yu, Wen-Yan; Tian, Yuan; Song, Yue; Gan, Ying-Ying; Guo, Meng-Wei; Ren, Xiao-Xuan; Li, Jia-Lin
Abstract : Waggle needling, a classical anti-spastic needling technique characterized by combination of acupuncture with joint movement, has gained increasing popularity of spasticity treatment in China. This study was designed to compare the anti-spastic effect of waggle needling to the routine needling and to explore its underlying mechanism. We established post-stroke spasticity model based on ischemia stroke operation (middle cerebral artery occlusion). Rats were divided into six groups: normal control group, sham-operated control group, ischemia stroke model group, waggle needling group, routine needling group and baclofen group. Neurological function and muscle tone were assessed by the Zea Longa score and modified Ashworth scale, respectively. Indirect muscle tone was testified with electrophysiological recording. Cerebral infarction was measured by 2, 3, 5-triphenyltetrazolium chloride staining. The concentrations and expressions of γ-aminobutyric acid transaminase (GABAT) and γ-aminobutyric acid (GABA) were detected by enzyme-linked immunosorbent assay and western blot assay. Waggle needling markedly alleviated neurological deficits, decreased cerebral infarction and eased muscle tone; simultaneously, attenuated GABAT and enhanced GABA expression in the cortical infarct regions in comparison with the routine needling ( P < 0.01), yet showed similar therapeutic effect to the baclofen group ( P > 0.05). These results preliminary supported that waggle needling as a potential promising non-pharmacological intervention for the treatment of cerebral ischemia and spasticity.